1969
DOI: 10.1139/v69-272
|View full text |Cite
|
Sign up to set email alerts
|

A 19F nuclear magnetic resonance investigation of the formation of Sb2F11 and SbnF5n+1 in the CsF–SbF5, t-butyl halide–SbF5, and tetraalkylammonium hexafluoroantimonate–SbF5 systems

Abstract: Fluorine nuclear magnetic resonance spectra have been obtained for the t-butyl fluoride–SbF5, t-butyl chloride–SbF5, tetraethylammonium hexafluoroantimonate–SbF5, and cesium fluoride–SbF5 systems, both with and without SO2 solvent. In SO2 solution the anion is Sb2F11− for all the systems, any remaining SbF5 being converted to SbF5•SO2. It is concluded that in the systems that do not contain SO2, higher polymeric anions SbnF5n+1−, where n > 2, are present. t-Butyl chloride and t-butyl fluoride give the t-but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

1970
1970
2008
2008

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 48 publications
(16 citation statements)
references
References 1 publication
1
15
0
Order By: Relevance
“…hexamethylbenzene are listed in Table 2. SbF5 co-ordinates strongly with the SOz solvent to give axial and equatorial fluorine ligands (28). The chemical shifts and observable fluorine spin coupling in this system are strongly temperature-and concentration-dependant, the present results being for concentrated room temperature solutions.…”
Section: 'mentioning
confidence: 55%
“…hexamethylbenzene are listed in Table 2. SbF5 co-ordinates strongly with the SOz solvent to give axial and equatorial fluorine ligands (28). The chemical shifts and observable fluorine spin coupling in this system are strongly temperature-and concentration-dependant, the present results being for concentrated room temperature solutions.…”
Section: 'mentioning
confidence: 55%
“…The basic methods of sample preparation have been described in earlier papers (3)(4)(5). For SbF5/SbC15/ S02C1F, SbF5/S02C12/S02CIF, and SbF5/COF2/S02-ClF, the antimony compounds were added from all glass syringes to suitably adapted n.m.r.…”
Section: Sample Preparationmentioning
confidence: 99%
“…In a previous paper (1) it was shown that when t-butyl fluoride is allowed to react with SbF, and the product is dissolved in SO, the solution contains the trimethylcarbonium ion, the Sb,F,,-anion, and the adduct SbF,. SO,.…”
mentioning
confidence: 99%